Happy paws - Fang, Vicky (Fang, Vicky. Layla and the Bots, 2020)
While Layla and her three Bots (Beep, Boop, and Bop) are setting up for their rock band's performance, she gets some bad news, Happy Days Amusement Park is closing; Layla thinks she has the perfect solution: turn the place into an amusement park for dogs--but the new rides have to pass a safety inspection before Happy Paws Amusement Park can open.